Epinephrine and glucagon effects on the second messengers cAMP and IP(3) in fish hepatocytes. - Gambarotta, Adriana. (University of Ottawa (Canada), 1994)
This thesis demonstrates the production of IP$\sb3$ and confirms the production of cAMP in eel and bullhead hepatocytes following exposure to either, epinephrine (EPI) or glucagon (GLU). These findings indicate the presence of both transduction systems at least in these two fish species. As in mammals, both hormones function by stimulating the production of different amounts of second messengers. In fish hepatocytes the production of these intracellular mediators was significantly less with GLU than with EFI. The activity of the enzyme adenylyl cyclase (ACase) was assessed to correlate the enzyme activities in crude membrane preparations with the production of cAMP in intact cells following EPI and GLU stimulation. Moreover the use of the adrenergic $\alpha$- and $\beta$-antagonists phentolamine and propranolol provided evidence for an effect of EPI on both $\alpha\sb1$- and $\beta\sb2$-adrenoceptors. The presence of the $\alpha\sb1-$subtype was confirmed in black bullhead and assessed for the first time in American eel liver membranes with the specific-binding of radioactive prazosin ($\sp3$H-PRZ), a classical $\alpha\sb1$-antagonist, and the displacement of $\sp3$H-PRZ with other non-radioactive, adrenergic antagonists. The order of potency displayed by these ligands was typical for $\alpha\sb1$-adrenoceptors of mammals. Similar affinity for PRZ was found in the two species, whereas eel showed less receptor density than bullhead membranes. However, the binding capacity was found to be within the range of the mammalian receptors. Moreover the existence of IP$\sb3$-binding sites, that may account for the involvement of a Ca$\sp{2+}$ messenger system in response to EPI and GLU action was assessed for the first time in fish hepatocytes. Eel and bullhead microsomal preparations showed different affinities and binding capacities for IP$\sb3.$ These results give support to the hypothesis that both hormones may induce intracellular Ca$\sp{2+}$ oscillations. (Abstract shortened by UMI.)
Keywords: Biology, Botany.